2019
DOI: 10.1136/bmjopen-2018-025080
|View full text |Cite
|
Sign up to set email alerts
|

Introducing physically active lessons in UK secondary schools: feasibility study and pilot cluster-randomised controlled trial

Abstract: ObjectivesAssess feasibility, acceptability and costs of delivering a physically active lessons (PAL) training programme to secondary school teachers and explore preliminary effectiveness for reducing pupils’ sedentary time.Design and settingSecondary schools in East England; one school participated in a pre-post feasibility study, two in a pilot cluster-randomised controlled trial. In the pilot trial, blinding to group assignment was not possible.ParticipantsAcross studies, 321 randomly selected students (51%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 55 publications
4
42
0
Order By: Relevance
“…This program did not demonstrate any effectiveness for reducing pupils' sedentary time on a full day or during school time in the short timeframe where pupils wore the accelerometers. The lack of results in reducing sedentary time in secondary schools is in accordance with a recently published pilot study from the UK, who found no evidence of reduced sedentary time after implementing PAL [55]. This indicates the importance of examining levels of PA and sedentary time as individual and independent constructs [66].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This program did not demonstrate any effectiveness for reducing pupils' sedentary time on a full day or during school time in the short timeframe where pupils wore the accelerometers. The lack of results in reducing sedentary time in secondary schools is in accordance with a recently published pilot study from the UK, who found no evidence of reduced sedentary time after implementing PAL [55]. This indicates the importance of examining levels of PA and sedentary time as individual and independent constructs [66].…”
Section: Discussionsupporting
confidence: 79%
“…In our study, the intervention group is stable over time in minutes spent in MVPA during school hours, where the control group declines. Similar results were found by Gammon et al [55] who implemented PAL in secondary schools [55]. Because of the general decline in PA levels from child to adolescent, it is argued that interventions that attenuate PA decline could be considered effective [56].…”
Section: Discussionsupporting
confidence: 68%
“…Only two studies were explicitly based on theory, namely the COM-B model of behaviour change 18 37 . One study presented a logic model of how it's physically active lesson intervention may impact student's sedentary behaviour and educational outcomes 47 . 33/42 studies reported interventions as delivered by existing classroom teachers (Table 1), with the remainder delivered by recruited personnel of teachers or researchers.…”
Section: Study Selectionmentioning
confidence: 99%
“…The social environment reflects the degree to which the stakeholders engage and support each other to provide physical activity. For example, teachers who implement physically active learning within supportive school social environments experience fewer implementation barriers [38][39][40].…”
Section: The Social and Physical Environmentmentioning
confidence: 99%